Kesenjangan Aspirasi Karir Antara Santri Pondok Pesantren Tahfizhul Quran dan Orang Tua - Ira Nurhuda Wati (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2025)
This research aims to increase the level of career aspirations of students. Guidance and counseling as an integral part of education that aims to help students of the Tahfidzhul Quran Islamic Boarding School in achieving optimal development, one of which is helping students achieve career development tasks, namely in making career decisions that are in accordance with what the students aspire to. This study uses qualitative methods and descriptive methods. The type of research conducted is in the form of case studies. The data source used by the researcher is the triangulation of sources from the data of each source. The primary subject of this research is students who experience career aspirations at the Tahfidzhul Quran Islamic Boarding School, which consists of three students. The data collection techniques used by the researcher are non participant observation, semi-structured interviews. Data analysis uses data reduction. The results of the research from three speakers show (1). General description: Most of the general descriptions of the career aspirations of Tahfizhul Quran Islamic Boarding School students from the three resource persons chose a career choice to work after graduating from the Islamic Boarding School. (2). Factors affecting the Gap: incompatibility with career aspirations between Tahfidzhul Quran Islamic Boarding School students and their parents, thus creating a gap between the two which is inseparable from biological, sociological, and psychological factors. (3). Impact of the gap: The impact of the gap in career aspirations of the three speakers such as the unfulfilled need for awards, the absence of opportunities and trust in themselves, and the emergence of feelings of disappointment towards their parents.